Dog's behaviour in 2-D animation - Lau, Kiew Toh, (Universiti Malaysia Sarawak (UNIMAS), 2013)
This research is about dog's behaviour in 2-D animation. The focus in this research is not only the creativity of storyline but also on the principles of animation and interesting visual and composition on animation. The final product is created in order to validate the effectiveness of the animation.